The Strategic Role of Muslim Entrepreneurs in Promoting Sharia Economic Growth - Davi Rahmad Aldi Alamsyah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
This research aims to understand the strategic role of Muslim entrepreneurs in developing the sharia economy. Muslim entrepreneurs have a strong moral and social responsibility in encouraging economic growth based on sharia principles. In an economy based on Islamic values, honesty, fairness, and transparency have a significant role. Through a qualitative approach, this study analyzes the roles and challenges faced by Muslim entrepreneurs and their contribution to the sharia economy in Indonesia. The results of the study show that Muslim entrepreneurs play an important role in providing job opportunities, expanding sharia-based markets, and building a sustainable economy. However, there are challenges in the form of market competition and a lack of adequate understanding of sharia economics among the public. Keywords : Muslim Entrepreneurs, Sharia Economic Growth, Sharia Economic Literacy